Leadership of the English Premier League Football Club Managers: A Case Study of Manchester United Football Club Management from 1986 To 2013 - Jaita, Yuttapoom; Chiangtung, Wanthiwa (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
This academic article aims to study the leadership of Sir Alex Ferguson, the manager of Manchester United Football Club (MUFC) who was able to manage the football club to achieve success by means of leading. His soccer team to be the winner of the Premier League match and also become the best soccer team that has held champion cups rather than others in the British Isles. The data were collected from academic articles, analysis and news made available on various media and then analyzed in conformity with concepts and theories of leadership. The data analysis was conducted for revealing its findings and providing guidance on other further studies. The findings revealed that Ferguson’s effective management of having achieved many phenomenal successes continuously from 1986 to 2013 as well as his leadership style can be summarized in 6 aspects as follows: Firstly, the creation of a youth team system for team development in a long term; Second, the ambition and desire to make a great success as a football club manager; Third, the leadership ability to persuade others; Fourth, the creation of mutual interaction by allowing the team members to meet [and discuss] him directly; Fifth, the importance of focusing attention on teamwork; and Finally, the cost-effective resource management of the football club.